Challenges of Jurisprudence in the Context of the Constitutional Law, as a Complete Base of legal regulation of the World Process - Ayvazyan, V. (Bulletin of Yerevan University C: Jurisprudence, 2019)
The main purpose of this article is to present the methodological tools based on the phenomenological synthesis of legal conflict resolution, on the basis of which the identification of the legal nature of the objects of legal regulation in the light of the consideration of law as a system of conflict prevention and resolution. The central unit is the system conflict, as a tool for finding a violation of the right to integrity of the system and determine the degree of solvency of the system of legal regulation in general and constitutional legal regulation in particular. One of the key weaknesses and causes generating Violations of system of law is the lack of consistent description of Genesis of Law at a fundamental level, allowing to bring the universalism of law, which allows, in turn, determine the system of law formation for objective quality criteria, and organizational forms of cross-relations within the society, the State, relations the outside world, in the metric of legal consolidation.
Keywords: Rule of law, Systemic Conflict, Genesis, Legal System, Constitutional-legal regulation, world process, global system